(untitled) (Research, Society and Development, 2022)
Weeds have become resistant to the herbicide Glyphosate resulting in a constant problem for coffee growers in Brazil. The use of herbicide mixtures with different mechanisms of action has been used aiming a better control of these plants. Therefore, the objective of this study was to evaluate the effect of applying Glyphosate in a mixture with different herbicides on the control of weeds in coffee plantations. Therefore, an experiment was conducted in the field, with six treatments and four repetitions, in a randomized block design. The plots were installed between the rows of coffee trees, each plot measuring 1m², and at least 1m apart. The following treatments were adopted: Glyphosate, Clethodim, Metsulfuron-methyl, Glyphosate + Clethodim, Glyphosate + Metsulfuron, Control (witness). Control and percentage of toxicity were evaluated at 7, 14 and 21 days after application. It can be seen that the mixture of Glyphosate + Metsulfurom-methyl showed better efficiency for the control of Bitter, Caruru and tiririca grass. The mixture of Glyphosate + Cletodim was efficient in the control of Cipó de veado. In relation to isolated applications, Metsulfuron-methyl stood out with better results in general